Knowledge action vs. creative action: Devices of contrast between old and new in the architectural heritage recovery project - Romagni, Ludovico; Porfiri, Simone (Frontiers in Built Environment, 2023)
In a Casabella editorial from a few years ago, dedicated to the recovery of the existing architectural heritage, Francesco Dal Co defined restorers as a corporation that considers itself the exclusive custodian of the knowledge, capable of scientifically resolving the conflicts that each restoration operation involves. Today the perception is that restorers practice a different profession from architects: more than twenty years ago Manfredo Tafuri noted that it was possible to observe a tendency towards the separation between restoration, and conservation. Although the shared idea is that architecture is the result of successive modifications and never offers a stable image: the action of alteration of the built, especially the historicized one, takes place by appealing only to the scientific nature of a rigorous method that mortifies the creative act by losing the poetic root of our discipline. This type of conviction has led the discipline of architectural restoration throguh the tendency to make the cognitive phase coincide with the creative phase: in which the work itself suggests the design act. The project does not alter the image of the place or of the historicized asset but activates a process of crystallization of the existing, which proclaims conservation action as the only possible way: a heroic act of resistance. In the current urban scenario characterized by the “built paradigm”, the new seems to be conceived exclusively as a derivation of the existing. Augè defined the contemporary city as an immense ruin (“city worksite”) in which the unfinished and abandoned fragments of the new constructions coexist with the ruins of the city of history as well as the ruins of the Modern. For that reasons, does it still make sense to distinguish the restoration project of a building from the project of a building? The contribution proposes a field of research that aims at the rapprochement between two disciplinary fields, architectural design and restoration, where the poetic root of the project returns to dialogue with the cognitive action on the asset and the application of scientific criteria for the consolidation and restoration of the elements.